Genetic screening for the next decade: application of present and new technologies. - McCabe, E. R. (Yale Journal of Biology and Medicine, 1991)
Molecular genetic technology is diffusing from the research laboratory to the clinical laboratory, where it has already begun to influence prenatal diagnosis and counseling. In the very near future, this technology will be applied more generally, using population-based screening strategies. Pilot programs are beginning to evaluate the technical feasibility and efficacy of recombinant DNA techniques for newborn screening follow-up. DNA-based population screening is being considered for heterozygous carriers of an autosomal recessive disorder such as cystic fibrosis in order to identify carrier couples at risk of having an affected child. We will review the current DNA methodologies in the context of three genetic disorders: sickle-cell disease, Duchenne muscular dystrophy, and cystic fibrosis. We will then consider the requirements for implementation of these new technologies. We will conclude that implementation will require two key factors: machines and people. Machines are required to automate molecular genetic procedures, which are currently personnel-intensive, so that the expense can be reduced and the procedures made more cost-effective. The people who are required are health professionals knowledgeable in the clinical aspects of the target disorders, as well as in the DNA laboratory testing. These professionals will be able to facilitate sample acquisition and information exchange among the laboratory, the primary health care provider, and the families requesting consultation.